Qur’anic Economic Character Education: Integrating Islamic Values And Modern Educational Philosophy In Secondary Schools - Zulkifli Sumantri; Kama Abdul Hakam; Encep Syarief Nurdin; Cece Rahmat; Imas Kurniawaty (Jurnal Indonesia Sosial Sains, 2025)
This study aims to develop a Qurani-based economic character education model through daily charity activities in senior high schools, integrating Islamic values with modern educational theories. The conceptual foundation draws from Surah Al-Baqarah (verses 261–269) and three authentic hadiths of Al-Bukhari (No. 6465, 2989, and 2442) that emphasize sincerity, consistency in good deeds, and social benefit, combined with modern educational theories. This research applies a qualitative conceptual literature study using Creswell and Miles & Huberman frameworks through stages of data reduction, display, and thematic conclusion. The findings reveal that daily charity functions as an effective medium for character formation through moral habituation, social interaction, and spiritual reflection. Key values such as sincerity, financial responsibility, empathy, and moderation in consumption are systematically developed, supporting SDG 4 (Quality Education) and SDG 12 (Responsible Consumption and Production). The novelty of this study lies in its integration of Qurani ethics and Western educational philosophy (Aristotle, Dewey, Maslow, and Vygotsky) into a contextual and applicable framework for strengthening economic character education in Indonesian secondary schools.